Adverse events following immunization and psychological distress among cancer patients/survivors following vaccination against SARS-CoV-2 infection - Wong, Li Ping; Lai, Lee Lee; See, Mee Hoong; Alias, Haridah; Syed Omar, Sharifah Faridah; Ng, Chong Guan; Ho, Gwo Fuang; Ong, Teng Aik; Wong, Yee Chi; Ooi, Po Lin; Elias, Jasmin Munchar; Hu, Zhijian; et al. (Frontiers in Psychology, 2022)
Purpose: This study aims to describe the adverse events following immunization (AEFIs) of SARS-CoV-2 vaccination in cancer patients/survivors associated with their psychological distress. Methods: A cross-sectional study was conducted to assess AEFIs after the receipt of SARS-CoV-2 vaccines in cancer patients/survivors attending a university hospital in Malaysia. Psychological distress was measured using the Hospital Anxiety and Depression Scale (HADS) before and after the first and second doses of COVID-19 vaccine. Results: A total of 217 complete responses were received. Compared with before vaccination, both HADS Anxiety (HADS-A) and HADS Depression (HADS-D) scores were significantly reduced after the first and second dose of the SARS-CoV-2 vaccine. Most of the participants had mild or moderate systemic and local AEFIs, with the most common being pain at the injection site, tiredness and headache for both the first and second doses of vaccine. Positive correlations between the total AEFI score and HADS-A (r = 0.309, p < 0.001) and HADS-D (r = 0.214, p = 0.001) scores were observed after the first dose of the SARS-CoV-2 vaccine. Similarly, positive associations were observed between the total AEFI score and HADS-A (r = 0.305, p < 0.001) and HADS-D (r = 0.235, p < 0.001) scores after the second dose of the SARS-CoV-2 vaccine. Conclusions: Mild-to-moderate AEFIs found in this study help address vaccine hesitancy in cancer patients/survivors. Receiving the SARS-CoV-2 vaccine had a positive effect on decreasing psychological distress in cancer patients/survivors. High severity of an AEFI was associated with higher anxiety and depressive symptoms.